DAMPAK PENGEMBANGAN KOMODITAS PERKEBUNAN TERHADAP PEREKONOMIAN PROVINSI JAMBI (Impact of the Development of Estate Crops on Economic Jambi Provinces) - Rizki Gemala Busyra (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Jambi is one of the central of estate crop productions in Indonesia. In 2006, the Minister of Agriculture issued the Regulation about Revitalization Program. Revitalization Program is an effort to accelerate the development of smallholders through expansion, renovation and rehabilitation of tree crops. Along with minister of agriculture policy, the Jambi province activities focused on the development commodity rubber, oil palm, coconut and coffee. The purpose of this study is to identify the factors that affect the area, production, productivity, commodity prices and export in the Jambi province, on each of the commodities (rubber, oil palm, coconut, coffee and Jambi), and to analyze the impact of development of commodities on the economy of Jambi province. This study employs an econometric model consisting of 17 structural equations and 9 identity equations. This study uses secondary data is structured as pooled annual data on nine districts in Jambi province, starting 2000 until 2009. The result of this study shows the only expansion of rubber and palm oil which can improve the economy of Jambi. The coconut and coffee does not have significant impact on the economy of Jambi.Keywords: Econometric Model, Estate Crops, Jambi Province